Emerging advancements for virtual and augmented reality in healthcare - Reis, Sara; Queiros, Ricardo; Coelho, Luis (IGI Global, 2022)
"The goal of this book is to show how to put Virtual Reality in action by linking academic and informatics researchers with professionals who use and need VR in their day-a-day work, with a special focus on healthcare professionals and related areas for the purpose of exchanging the knowledge, information and technology from the international communities in the area of VR, AR and XR.